Antifouling nanocomposite polymer coatings for marine applications: A review on experiments, mechanisms, and theoretical studies. (10th August 2022) - Pourhashem, Sepideh; Seif, Abdolvahab; Saba, Farhad; Nezhad, Elham Garmroudi; Ji, Xiaohong; Zhou, Ziyang; Zhai, Xiaofan; Mirzaee, Majid; Duan, Jizhou; Rashidi, Alimorad; Hou, Baorong
Highlights: Experimental studies about antifouling nanocomposite polymer coatings are reviewed. Antifouling mechanisms of nanocomposite polymer coatings are presented. Metal oxides, metal-organic frameworks, nano-carbons, MXene, and clay are discussed. Theoretical and simulation studies for antifouling investigations are introduced. Antifouling behavior is simulated by quantum computations and intermolecular forces. Abstract: Marine fouling is a worldwide challenge with huge damages on industrial structures, side effects on economics of industries, and environmental and safety-related hazards. Different approaches have been used for combating fouling in the marine environment. Meanwhile, nanocomposite polymer coatings are a novel generation of antifouling coatings with merits of toxin-free chemical composition and ease of large-scale application. Nanomaterials such as nano-metals, nano-metal oxides, metal-organic frameworks, carbon-based nanostructures, MXene, and nanoclays have antibacterial and antifouling properties in the polymer coatings. Besides, these nanomaterials can improve the corrosion resistance, mechanical strength, weathering stability, and thermal resistance of the polymer coatings. Therefore, in this review paper, the antifouling nanocomposite coatings are introduced and antifouling mechanisms are discussed. This review explicitly indicates that the antifouling efficiency of the nanocomposite coatings depends on the properties of the polymer matrix, the inherent properties of the nanomaterials, the weight percent and the dispersion method of the nanomaterials within the coating matrix, and the chemicals used for modifying the surface of the nanomaterials; meanwhile, the hybrids of different nanomaterials and appropriate chemical agents could be used to improve the antifouling behavior of the prepared nanocomposites. Moreover, the theoretical studies are introduced to pave the way of researchers working on the antifouling coatings, and the importance of the theoretical studies and computational modeling along with the experimental research is notified to develop antifouling coatings with high efficiency. Graphical abstract: Image, graphical abstract .